Analysis of the Level of Public Understanding in the Preparation of the Simalungun Regency Regional Revenue and Expenditure Budget - Putri Afdillah; Andri Soemitra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
Public comprehension of the Regional Revenue and Expenditure Budget in Simalungun Regency is the obligation of the Simalungun Regency Government. Provincial advancement arranging as per neighborhood conditions expects to reply and is planned so local improvement arranging is obliging to the elements and goals of the local area, with the goal that it can successfully and proficiently understand the local vision, to be specific monetary recuperation, improvement of APBD act. Local area desires and support are appeared as immediate association in territorial planning arranging gatherings and the consequences of top to bottom meetings with data that one might say that the peculiarity of local area cooperation in the APBD readiness process in Simalungun Regency can normatively be supposed to be as per the instrument managed in Law no. 25 of 2004. Regarding the execution of the support of individuals of Simalungun Regency with the most common way of setting up the APBD.